The Integration Challenges of Female Refugees and Migrants: Where Do We Stand? - Clara Albrecht; Maria Hofbauer Pérez; Tanja Stitteneder (CESifo Forum, 2021)
The challenge of integrating migrants and refugees is a widely known and discussed topic among policymakers within the EU, though a comprehensive gender-specific approach is still lacking. Migrant women and especially refugees deserve special attention, since nearly every second migrant and every third asylum seeker is female. However, many of these women are poorly educated, lack work experience and labor market participation. In this article, we examine gender-specific challenges of female migrants and refugees and look at strategies and existing initiatives suitable for overcoming obstacles and promoting their integration into host country labor markets and societies.
Keywords: 330